CSC405: Computer Application / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course is aimed at giving the student a wide knowledge on database management system and their use in modelling information in the real world. The conceptual, logical and physical levels of database design are discussed. The course will cover both the theoretical and practical aspects of database systems. The main emphasis will be on the formation of a database system. This will require students to develop a database system starting from the entity-relationship model up through implementing their system using a relational database, Microsoft Access 2013.